Attitude and vibration control with double-gimbal variable-speed control moment gyros. (November 2018) - Sasaki, Takahiro; Shimomura, Takashi; Pullen, Sam; Schaub, Hanspeter
Abstract: The attitude and vibration control of a flexible spacecraft with two parallel double-gimbal variable-speed control moment gyros (DGVSCMGs) is considered. The coupled nonlinear equations of motion create a complex challenge in a pointing control development. First a Gain-Scheduled (GS) controller for a 3-axis attitude control is designed by the post-guaranteed linear matrix inequalities (LMIs) method with H 2 / H ∞ constraints. Next an H 2 / H ∞ controller for vibration control is designed to attain both attitude and vibration control at the same time. The two controllers are combined using the dynamic inversion (DI) technique. Finally, the effectiveness of the proposed combined controller is demonstrated through a numerical example. Highlights: Develop the dynamics of a flexible spacecraft with multiple DGVSCMG actuators. Design the gain-scheduled controller using the post-guaranteed LMI method. Propose the combined controller for attitude and vibration control using the DI technique. Design the singularity avoidance steering law for DGVSCMGs. Demonstrate the effectiveness of the proposed approach through numerical simulations.